Analisis Best Practice Kebijakan Carbon Tax Dalam Mengatasi Eksternalitas Negatif Emisi Karbon Di Indonesia - Aranta Prista Dilasari; Heti Nur Ani; Rahma Jariatul Hajah Rizka (Owner : Riset dan Jurnal Akuntansi, 2023)
The purpose of this study is to analyze the design of the carbon tax policy that will be applied in Indonesia, as well as to analyze and provide an overview of the best practice of implementing carbon tax in Indonesia. The analysis used is based on existing field facts and confirmed by existing theories and regulations. The data analysis method used in this study is descriptive or comparative analysis with a practical approach methodology, namely comparing carbon tax policies in several countries to be used as a reference in making the ideal carbon tax formulation and the mechanism for implementing carbon tax in Indonesia. The results of this study indicate that the application of CO2 tax is basically suitable to be applied in Indonesia. The first reason refers to the study of the International Monetary Fund (IMF) and OECD, carbon tax can be one of the policy options available as a revenue stream because the pandemic puts pressure on tax revenues. Second, the CO2 tax is directed to climate protection and becomes an environmental protection tool. His methods of reducing negative externalities are in line with the principles of sustainable development. Third, many countries have introduced carbon taxes, including countries in Europe and others. However, the implementation of the carbon tax has not been implemented in Indonesia, this can be seen from the negative impacts of the implementation of the carbon tax. In addition, the results of the analysis show that gross domestic product (GDP), real consumption, and employment (employment) are predicted to be lower, if the policy is implemented without any follow-up actions taken, this will certainly cause negative pressure on all macro variables economy.